Utilizing multiple scattering effect for highly sensitive optical refractive index sensing - Tran, Vinh (2022)
The sensitivity of random optical diffraction to refractive index inhomogeneity is usually considered as a challenging obstacle for imaging or controlling light through scattering media. Here, on the opposite side, we utilize the natural randomness of strongly scattering media and their sensitivity to refractive index inhomogeneity to develop a novel optical sensor. Unlike various sensing technologies with trade-off between complexity and sensitivity, we demonstrate a very simple sensing technique, which uses just ground glass optical diffusers to achieve very high sensitivity. Light propagating through a scattering medium is scattered multiple times at multiple interfaces between ground glass and the surrounding environment creating a speckle pattern, which is sensitive to the environment's refractive index. The correlation of speckle patterns indicates the change of refractive index around the scattering medium. Simply placing the rough surface of ground glasses in contact with sensing solution, we are able to detect the solution's refractive index change at resolution of 3.87 × 10−6 RIU, which is equivalent to the glucose concentration change of 12 ppm. More interestingly, the sensitivity of the proposed approach could be improved simply by adding more scattering surfaces in contact with the target medium. Our simple technique could be very useful for prominent applications in refractive index sensing such as measuring concentration of solution or gas.